Validation of a modified life-space assessment in multimorbid older persons with cognitive impairment - Ullrich, Phoebe; Werner, Christian; Bongartz, Martin; Kiss, Rainer; Bauer, Jürgen M.; Hauer, Klaus (The gerontologist, 2019)
AbstractBackground and Objectives. To investigate the validity, reliability, sensitivity to change, and feasibility of a modified University of Alabama at Birm
Published: 31 January 2018
Gesehen am 21.05.2019